(untitled) (Damascus University Journal for legal sciences, 2025)
God Almighty created the world and He created it not for a purpose upon which creativity is based, nor for a wisdom upon which creation depends. Rather, everything He created of good and bad, benefit and harm was not for a purpose that led him to it, nor for a purpose that made the action obligatory upon Him, Glory be to Him. He has the right to do whatever he wants and rule by what he wants, in contrast to the Mu’tazilah, because they stoned God Almighty in his actions and obligated him to take care of the fittest, and that he must do what is righteous and what is best for his servants, and God does for his servants what is best, but none of his servants obliges him to do that, and we will see Through research, the Mu’tazilites did not mean obligation in the algebraic sense that we use among ourselves.